Papuan EFL Students’ Perception in Using Deactivate Read Receipts of WhatsApp during Students and Lecturer’s Communication - Wulandari, Sefia Putri; Sahib, Rahmawansyah; Nugroho , Anggit Prasetio (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
The use of the deactivate read receipts feature has become increasingly common among various groups, including students. However, its use has sparked both positive and negative responses. This study aims to investigate students’ perceptions of this feature within the context of academic communication, particularly in interactions with lecturers. Moreover, it explores the implications arising from deactivating read receipts in such communication. Employing a descriptive qualitative approach, the study involved twelve EFL students and four lecturers as participants. Data were collected through online observation and semi-structured interviews. Online observation involved gathering screenshots of chat interactions between students and lecturers, while interviews were conducted using an interview guide and audio recordings. The collected data were analyzed using discourse analysis, comprising four stages: data recording, transcription, selection, and interpretation. The findings reveal three dimensions of student perception. First, the cognitive dimension reflects that the feature is perceived as impolite in academic contexts but considered normal in non-academic contexts. Second, the affective dimension shows that it can evoke both emotional discomfort and neutrality. Third, the conative dimension includes tendencies toward message resending and communication uncertainty. Additionally, the deactivation of read receipts has been found to lead to miscommunication and foster negative assumptions on the part of the message recipient toward the sender. Consequently, further research is recommended to explore this phenomenon in greater depth.